Awareness Factors Affecting Contraceptive Uptake in women attending the Gynaecology Out-Patients Department, at a Tertiary Hospital - Ndlovu, Sinegugu (University of the Witwatersrand, Johannesburg, 2023)
Objectives: The objectives of the study were to assess the knowledge and awareness of contraception in the women seen at Chris Hani Baragwanath Academic Hospital Gynaecology Out-patient department. We also looked at the efficiency of contraceptive counselling from the health care providers and assessed patient satisfaction. Study design: We conducted a prospective, descriptive, cross-sectional study. A survey of 100 women, of reproductive age attending the gynaecology out-patient department, was conducted using a questionnaire over a period of 3 months. Sample size was determined by use of The Survey System, Sample Size Calculator. The survey assessed the women’s knowledge regarding barrier methods as well as hormonal methods (in the form of combined oral contraceptives, injectables, the implant, the intrauterine device, emergency contraception) and permanent forms of contraception. Independent variables were age, level of education, employment, parity. Dependant variables were prevalence of contraceptive uptake, knowledge of available contraception. The association between the prevalence of contraceptive uptake and the knowledge regarding the available methods of contraception was assessed using the Chi square test, as well as the Mann Whitney U test. A p-value of 0.05 was decided upon for statistical significance an odds ratio and 95% confidence intervals were reported. Results: Overall Our study found that the total percentage of women using a method of contraception was 39.79 % while those that were not on any method of contraception was 60.20%. Our study also found that there were high rates of discontinuation of contraception. Overall,there was poor contraceptive awareness and knowledge. There was more awareness than there was intricate knowledge regarding the different forms of contraception. Contraceptive counselling increased the rate of contraceptive uptake; of the women that were initially counselled, and then offered contraception, 82.9% of them were agreeable. Conclusion: Awareness does not equal knowledge. All gynaecology out-patient visits should be seen as an opportunity for contraceptive counselling, regardless of the main complaint. The high rate of discontinuation of hormonal contraception should be further assessed, and women should be counselled prior to discontinuation, and preferably placed on another form of contraception which suits their needs
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine, in the field of Obstetrics and Gynaecology to the faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg, 2023
Keywords: Gynaecology; Contraceptive uptake; UCTD; SDG-3: Good health and well-being